Natural hydrogen migration along thrust faults in foothill basins: The North Pyrenean Frontal Thrust case study. (October 2022) - Lefeuvre, N.; Truche, L.; Donzé, F.-V.; Gal, F.; Tremosa, J.; Fakoury, R.-A.; Calassou, S.; Gaucher, E.C.
Abstract: The existence of geological fluids rich in natural hydrogen (H2 ) raises the question about the energy potential of this carbon-free resource. However, to date there is no exploration strategy based on robust methodologies and pathfinders. Therefore, it is important to develop an exploration guide that is not only focused on surface gas monitoring, but that also considers the local deep geological setting integrating the entire hydrogen system from source to trap or leakage into the atmosphere. The northwestern Pyrenees, and particularly the Mauléon Basin, represent a promising geological environment for natural H2 exploration for at least four reasons. First, an ultramafic mantle body is emplaced at shallow depth below the basin under pressure-temperature conditions favorable to serpentinization. Second, major faults such as the North Pyrenean Frontal Thrust constitute large-scale fluid flow convergence and drainage. Third, hydraulic gradients imposed by sharp reliefs and combined with temperature and pressure gradients trigger fluid migration. Fourth, impermeable sedimentary formations or caprocks such as evaporites or claystones overly porous reservoir rocks that could constitute traps for accumulating H2 . To investigate H2 migration at the fault scale, we present new geochemical and geophysical data recorded along the North Pyrenean Frontal Thrust. Based on both soil gas and electromagnetic transects, we reveal the presence of a gas-draining fault. Soil gas concentration (H2, CO2, CH4 and 222 Rn) recorded at 1 m depth increases when approaching the North Pyrenean Frontal Thrust. The maximum H2, CO2 and 222 Rn concentrations recorded in the fault zone are 822 ppmv, 10.3 vol% and 57 kBq.m −3, respectively - whereas their local background concentrations are by 1–2 orders of magnitude lower: 10 ppmv, 0.2 vol% and 0.3 kBq.m −3 respectively. Our geochemical and geophysical data support the concept of a deep-fluid migration along the detected fault plane. In addition, the study of historical well data combined with the most recent geological and geophysical surveys carried out in the region, highlights zones where H2 could accumulate at depth. The Triassic salt formations, located at 2800 to 4000 m deep beneath the Mauléon Basin, represent the most promising trap for H2 in the northwestern Pyrenees. Graphical abstract: Image 1 Highlights: The western Pyrenees as a fertile geological setting for H2 production and migration. Soil gas and geophysical surveys carried out to detect gas migration. A deep-fluid migration along the North Pyrenean Frontal Thrust (NPFT).